2009
DOI: 10.3109/01480540903286468
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidant effect of vitamin C coadministration with bisphenol A, nonylphenol, and octylphenol on the reproductive tract of male rats

Abstract: This study was performed to investigate whether bisphenol A (BPA), nonylphenol (NP), and octylphenol (OP) induce oxidative stress on the reproductive tract of male rats and if coadministration of vitamin C can prevent any possible oxidative stress. Wistar male rats were divided into seven groups as control (vehicle; olive oil), BPA, NP, OP, BPA+C, NP+C, and OP+C. BPA, OP, and NP groups (25 mg/kg/day) were administered orally to rats three times a week for 45 days. In BPA+C, NP+C, and OP+C groups, vitamin C (60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 61 publications
7
32
0
Order By: Relevance
“…Korkmaz et al [5] showed an increase in TBARS level in liver of rats exposed to BPA. Similarly, previous studies show increased in the TBARS levels in the brain, testes, and kidneys of male rats exposed to BPA dose [5, 31, 32]. The increase in GSH level is important for GSHPx, which requires GSH as a cofactor, and the elevation in GSH level increases activity of GSHPx.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Korkmaz et al [5] showed an increase in TBARS level in liver of rats exposed to BPA. Similarly, previous studies show increased in the TBARS levels in the brain, testes, and kidneys of male rats exposed to BPA dose [5, 31, 32]. The increase in GSH level is important for GSHPx, which requires GSH as a cofactor, and the elevation in GSH level increases activity of GSHPx.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, in other organs ROS were induced when BPA was administered during the embryonic and infancy [11, 14, 30]. Similarly, others demonstrated that BPA generates ROS that causes oxidative damage in the brain, reproductive tract, and kidney of rats [5, 31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…This can typically be a result of increased lipid peroxidation due to oxidative stress. Moreover, BPA stimulates the generation of MDA in testis tissues (5) and testicular MDA concentrations were also altered due to BPA treatment in our study. The increase in MDA levels in the testicular tissue because of BPA exposure could be due to the production of more ROS and therefore, oxidative stress than normal as a result of BPA (42).…”
Section: Tab 1 Effects Of Oral Bisphenol a (Bpa) Administration On supporting
confidence: 62%
“…As Aikawa et al (2004) reported, deterioration of sperm motility and morphology caused by exposure to BPA was reduced by the administration of 1,000 IU of retinol acetate. Chitra et al (2003b) noted that coadministration with vitamin C had a protective effect against BPA-induced toxicity in epididymides and spleen of rats, whereas Aydogan et al (2010) did not find significant changes in sperm count and morphology after such exposure.…”
Section: Discussionmentioning
confidence: 94%